PENGARUH PERSEPSI SISWA TENTANG PROSES PEMBELAJARAN GEOGRAFI TERHADAP MINAT DAN HASIL BELAJAR DI SMA NEGERI 5 GORONTALO - Ismail, Rumiati; Lihawa, Fitryane; Rusiyah, Rusiyah (Jurnal Samudra Geografi, 2024)
The purpose of this study is to examine: 1) The effect of students' perception about geography learning process on students' interest in learning at SMA Negeri 5 Gorontalo. 2) The effect of students' perception about geography learning process on students' learning outcomes in SMA Negeri 5 Gorontalo. This research is a type of research using a quatitative approach. The data collection method used is survey method. The subjects of this study were students of class XI and XII social studies of SMA Negeri 5 Gorontalo in the academic year 2023/2024 totaling 80 students. Data collection techniques used questionnaires for student perception variables and learning interests while documentation for learning outcomes variables. Prerequisite test analysis consists of normality test, homogeneity test and autocorrelation test. Hypothesis testing consists of simple linear regression test and coefficient of determination test. The research results obtained: 1) There is a significant influence between the variable of student perceptions of the learning process on the variable of student interest in learning at SMA Negeri 5 Gorontalo, indicated by the calculation of significance obtained t value 6.186> t table 1.991 and Sig value. 0.000 < 0.05 2) There is a significant influence between the variable of students' perception of the learning process on the variable of students' interest in learning at SMA Negeri 5 Gorontalo indicated by the calculation of significance obtained t value 2.456 > t table 1.991 and Sig value. 0.016 < 0.05, so it can be concluded that there is a significant influence between students' perceptions of the geography learning process on student interest and learning outcomes at SMA Negeri 5 Gorontalo.